The Blockbuster Biopic Bohemian Rhapsody as an Expression of Cinema/Music Synergy - Radošinská, Jana; Točená, Zuzana; Rusňáková, Lenka; Schwarz, Martin (Communication Today, 2023)
The study focuses on Bohemian Rhapsody (2018, directed by Bryan Singer, later Dexter Fletcher), the biographical drama that reflects on the extraordinary lives and career patterns of the four members of the rock band Queen, predominantly the band’s frontman, Freddie Mercury. Given the fact that this feature film has changed the way we perceive the economic potential of biopics entirely, we offer an overview of some of the reasons why it was so successful in terms of the globalised film industry. The main objective of the study is to outline the biographical drama’s synergistic tendency in relation to the movie industry and the music business. Acknowledging Bohemian Rhapsody’s unprecedented global success, we work with the assumption that certain biographical dramas can, in fact, become globally popular, partly thanks to the fact that they utilise music as a nostalgia-driven narrative tool making portrayals of musicians deeper and more complex. The assumption is addressed via a theoretical reflection on the given topic and through a qualitative content analysis of the biographical drama Bohemian Rhapsody.